De Sekia a Ejea: la evolución lingüística de un topónimo controvertido (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The toponym sekia, SEGIA is one of the old toponyms which have been most problematic. One of these problems has been to determine if the toponym sekia, SEGIA is related to the current name of the village Ejea de los Caballeros (Zaragoza). However, most of these discussions have their origin in Ramón Menéndez Pidal's opinion, who, in 1948 pointed out that the toponym Exea -medieval form of Ejea- came from the Basque form etxea, 'house', interpretation which has been useful to establish a lot of his- torical and linguistic deductions. In this work we clean, to begin with, the forms under which the toponym appears, and later we show how the current from the old forms sekia, SEGIA, which will lead us to refuse Menéndez Pidal's interpretation.
Keywords: Toponymy; sekia; SEGIA; Ejea de los Caballeros; Etxea